The Onion presents Christmas exposed holiday coverage from America's finest news source (Philadelphia, PA Quirk Books, 2011)
Presents humorous and satirical newspaper headlines and articles relating to Christmas, covering such topics as Secret Santas, family dinner, office parties, holiday drinking, religious observance, and gift giving.
Keywords: Christmas -- Humor